Changes in complement alternative pathway components, factor B and factor H during dengue virus infection in the AG129 mouse. (7th March 2021) - Cabezas-Falcon, Sheila; Norbury, Aidan J.; Hulme-Jones, Jarrod; Klebe, Sonja; Adamson, Penelope; Rudd, Penny A.; Mahalingam, Suresh; Ong, Li-Ching; Alonso, Sylvie; Gordon, David L.; Carr, Jillian M.
Abstract : The complement alternative pathway (AP) is tightly regulated and changes in two important AP components, factor B (FB) and factor H (FH) are linked to severe dengue in humans. Here, a mouse model of dengue was investigated to define the changes in FB and FH and assess the utility of this model to study the role of the AP in severe dengue. Throughout the period of viremia in the AG129 IFN signalling-deficient mouse, an increase in FB and a decrease in FH was observed following dengue virus (DENV) infection, with the former only seen in a model of more severe disease associated with antibody-dependent enhancement (ADE). Terminal disease was associated with a decrease in FB and FH, with greater changes during ADE, and accompanied by increased C3 degradation consistent with complement activation. In silico analysis of NFκΒ, signal transducer and activator of transcription (STAT) and IFN-driven FB and FH promoter elements to reflect the likely impact of the lack of IFN-responses in AG129 mice, demonstrated that these elements differed markedly between human and mouse, notably with mouse FH lacking NFκΒ and key IFN-stimulated response elements (ISRE), and FB with many more NFκΒ and STAT-responsive elements than human FB. Thus, the AG129 mouse offers utility in demonstrating changes in FB and FH that, similar to humans, are associated with severe disease, but lack predicted important human-specific and IFN-dependent responses of FB and FH to DENV-infection that are likely to regulate the subtleties of the overall AP response during dengue disease in humans.